2020
DOI: 10.1002/jcp.30021
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study and multipurpose role of the CLV3/ESR‐related (CLE) genes family in plant growth and development

Abstract: The CLAVATA3/endosperm surrounding region‐related (CLE) is one of the most important signaling peptides families in plants. These peptides signaling are common in the cell to cell communication and control various physiological and developmental processes, that is cell differentiation and proliferation, self‐incompatibility, and the defense response. The CLE signaling systems are conserved across the plant kingdom but have a diverse mode of action in various developmental processes in different species. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 180 publications
(279 reference statements)
0
2
0
Order By: Relevance
“…Although the overall sequence conservation of SiCLE peptides is limited, they have a molecular weight of less than 15 kDa, and most of the polypeptides are highly basic and possess signal peptides at the N-terminal. This molecular characteristic is highly similar to CLE polypeptides found in other species [48,72]. Although these SiCLE genes exhibit diverse structural features, they all possess a conserved CLE domain located at the C-terminal, which is crucial for the functional specificity of the CLE family [73].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although the overall sequence conservation of SiCLE peptides is limited, they have a molecular weight of less than 15 kDa, and most of the polypeptides are highly basic and possess signal peptides at the N-terminal. This molecular characteristic is highly similar to CLE polypeptides found in other species [48,72]. Although these SiCLE genes exhibit diverse structural features, they all possess a conserved CLE domain located at the C-terminal, which is crucial for the functional specificity of the CLE family [73].…”
Section: Discussionsupporting
confidence: 61%
“…The whole genome was comprehensively analyzed using HMM search and multiple rounds of BLASTP to identify genes with a significance threshold of E < 10 −5 . Candidate genes with a sequence length exceeding 300 amino acids were excluded based on CLE gene characteristics [48]. Furthermore, candidate peptide sequences that contained the conserved CLE motif at the C-terminus were retained after motif prediction using MEME [42].…”
Section: Identification Of the Sicle Genes In Foxtail Milletmentioning
confidence: 99%
See 1 more Smart Citation
“…CLV3 is the member of endosperm surrounding region (CLE) gene family, which codes for small amino acid peptides having a conserved C-terminal sequence and CLE motif containing specific receptors for signaling. Molecular analysis reveals that overexpression of CLE peptides leads to retardation of root growth and premature root meristem differentiation that indicates a pathway related to CLV [47,48]. Similarly, it has been reported that a gene family member of cellulose synthase CESA1/RSW1 regulates the growth of root and shoot cell walls and determines cell shape during cell division and expansion in embryo cells of Arabidopsis [49].…”
Section: Rks and Stress Conditionsmentioning
confidence: 86%
“…CLV1 receptor kinases activated by small ligand binding molecules CLV3, which is secreted by central zone stem cells. Findings reveal that mutation in anyone of these mentioned genes can cause defects in development of stem cells and hence, control the growth of plant [47]. CLV3 is the member of endosperm surrounding region (CLE) gene family, which codes for small amino acid peptides having a conserved C-terminal sequence and CLE motif containing specific receptors for signaling.…”
Section: Rks and Stress Conditionsmentioning
confidence: 99%